Pengaruh Rasio Likuiditas dan Leverage terhadap Dividend Payout Ratio pada Badan Usaha Milik Negara yang Terdaftar di Bursa Efek Indonesia Periode 2023-2024 - Dika Wisnu Pratama; Febry Fabian Susanto (AKUA: Jurnal Akuntansi dan Keuangan, 2025)
This study examines the influence of liquidity and leverage ratios on dividend payout policies among Indonesian State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange from 2023 to 2024, aiming to understand how internal financial indicators shape dividend decisions within state-controlled corporations, thereby balancing profitability and public objectives. Using an explanatory quantitative approach with panel data regression on 40 SOEs at a 10% significance level, the research finds that the Quick Ratio positively and significantly affects the Dividend Payout Ratio, while the Debt-to-Equity Ratio shows a significant adverse effect; meanwhile, the Current Ratio and Debt-to-Asset Ratio exhibit no statistical significance. The model explains 98.62% of dividend payout variations, emphasizing that liquidity quality and capital structure remain critical in shaping SOE dividend policy. This study enriches corporate finance literature by contextualizing dividend behavior within state-owned entities in emerging economies. Practically, the findings offer valuable insights for policymakers and SOE executives in developing dividend frameworks that strike a balance between financial sustainability and fiscal contributions to the state. However, the study’s limited observation period and narrow focus on financial ratios call for further exploration, integrating governance, macroeconomic, and institutional factors.